2007
DOI: 10.1152/ajpcell.00127.2007
|View full text |Cite
|
Sign up to set email alerts
|

PKCδ mediates anti-proliferative, pro-apoptic effects of testosterone on coronary smooth muscle

Abstract: Sex hormone status has emerged as an important modulator of coronary physiology and cardiovascular disease risk in both males and females. Our previous studies have demonstrated that testosterone increases protein kinase C (PKC) delta expression and activity in coronary smooth muscle (CSMC). Because PKCdelta has been implicated in regulation of proliferation and apoptosis in other cell types, we sought to determine if testosterone modulates CSMC proliferation and/or apoptosis through PKCdelta. Porcine CSMC cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 54 publications
(92 reference statements)
1
27
0
1
Order By: Relevance
“…In agreement with our results, Bowles et al (5) showed that in VSMCs isolated from pig coronaries, testosterone treatment increases approximately fourfold caspase-3 activity, an effect inhibited by PKC-␦ small interfering RNA. Decreased expression of TNF-␣, IL-1␤, IL-6, p38 MAPK, caspase 1, 3, and 11 and increased expression of the antiapoptotic protein Bcl-2 have been reported in castrated and flutamide-treated rats after acute myocardial ischemiareperfusion (64), suggesting proapoptotic and proinflammatory effects of testosterone in the heart.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our results, Bowles et al (5) showed that in VSMCs isolated from pig coronaries, testosterone treatment increases approximately fourfold caspase-3 activity, an effect inhibited by PKC-␦ small interfering RNA. Decreased expression of TNF-␣, IL-1␤, IL-6, p38 MAPK, caspase 1, 3, and 11 and increased expression of the antiapoptotic protein Bcl-2 have been reported in castrated and flutamide-treated rats after acute myocardial ischemiareperfusion (64), suggesting proapoptotic and proinflammatory effects of testosterone in the heart.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, pretreatment of keratinocytes with NPS2143, an inhibitor of GPRC6A, completely blocked testosterone-induced apoptosis (data not shown). Because activation of caspase-3 is a hallmark of apoptosis, we measured caspase-3 activity in response to testosterone (34,36,40). The incubation of epidermal keratinocytes with testosterone revealed increasing caspase-3 activity in response to testosterone (Fig.…”
Section: Effect Of Downstream Signaling Network Of Gprc6a On H 2 O 2mentioning
confidence: 99%
“…PKCd is a key mediator in cell differentiation and inhibition of proliferation in various tissues (31)(32)(33)(34). A direct binding of ingenol mebutate to PKC isoforms has been observed (22).…”
Section: Discussionmentioning
confidence: 99%